Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial dan Kepemilikan Asing terhadap Kinerja Perusahaan Sub-Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Nur Anisah; Ulil Hartono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Company performance is an achievement obtained by individuals or groups within a company. The company's primary purpose is to increase the value of the company and the prosperity of the owners or shareholders. In achieving company goals, company performance is very decisive. This study aims to determine the effect of ownership structure on company performance. The independent variables used in this study consisted of institutional ownership, managerial ownership, and foreign ownership. This research used associative research. The population used in this study are textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used in this study was purposive sampling, resulting in 17 companies as samples in the textile and garment sub-sector companies. Furthermore, this study was analyzed using multiple linear regression analysis. The results of this study indicate that institutional ownership, managerial ownership, and foreign ownership do not affect company performance. In this regard, the company should maintain and increase the number of owners to manage its assets optimally.